Perspective on ophthalmic support in countries of the developing world. (30th October 2012) - Muecke, James; Sia, David IT; Newland, Henry; Casson, Robert J; Selva, Dinesh
Abstract There are over 300 million people living in the world today who are visually impaired and a further 45 million who are blind. The large majority (90%) of these people live in developing countries, and up to 75% of blindness are avoidable. With cataracts being the major cause of blindness and visual impairment, many ophthalmic aid programmes are aimed at alleviating the enormous burden caused by this readily treatable disease. Having said that, caution should be exercised that short surgical visits to remote rural areas that are not coordinated with local national eye care managers should be discouraged because they do little for the development of sustainable eye care programmes. With this in view, it has become imperative to design blindness prevention and ophthalmic support programmes that are workable, comprehensive, economical and sustainable.